CHARACTERISTICS OF MACROSCOPIC FUNGI IN PULAU MAS POPAYA RAJA NATURAL RESERVE OF GORONTALO UTARA - Safri Muhaimin Datau; Ani M. Hasan; Herinda Mardin; Wirnangsi Din Uno; Febriyanti (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2023)
The study aims at identifying the properties and number of macroscopic fungi species from the Ascomycetes and Basidiomycetes divisions within the Mas Popaya Raja Natural Reserve Island of Dunu Village, Monano Sub-district of Gorontalo Utara. Information on the results of this research can be used as fungi inventory data for the Agency for the Conservation of Natural Resources Conservation Section II of Gorontalo. This research employs an explorative survey method to directly observe the existence of macroscopic fungi within the natural reserve. The study is implemented in sequence, initial observation within the natural reserve to determine the sampling points, followed by identification of those macroscopic fungi based on the morphology of those fungi. Qualitative descriptive method is used to analyze the data by describing the properties of those macroscopic fungi in their habitats. This study has shed light on ten types of macroscopic fungi available in this natural reserve namely: Aleuria aurantia, Xylaria papyrifera, Microporus xanthopus, Lentinus sajor-caju, Ganoderma lucidium, Ganoderma applanatum, Rigidoporus sp, Maramius androcaseus, Lichenomphalia umbellifera, Scleroderma sinnamariense. The fungi found were dominated by the Basidiomycota division of the Agariomycetes class.